Improved Time Responses of PI & FL Controlled SEPIC Converter based Series Resonant Inverter-fed Induction Heating System - Muthu Periyasamy; Chandrahasan Umayal (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This work deals with the Power Factor Corrected Single-Ended Primary Inductor Converter (PFC-SEPIC) based voltage fed closed loop full bridge series resonant induction heating system for household induction heating applications. The output voltage of the front end PFC-SEPIC converter fed series resonant inverter governs the controllers, which may be PI controller or Fuzzy Logic Controller (FLC). The analysis and comparison of time responses are presented in this paper. The PFC-SEPIC converter is used to improve the output power and the THD of source side current are compared for PI and FLC controllers. PFC-SEPIC converter maintains improved current and voltage at unity power factor through the input mains. The SEPIC converter based Voltage Fed Full Bridge Series Resonant Inverter (VFFBSRI) converts the voltage at a frequency of 10 kHz to a level suitable for household induction heating. A 1 kW SEPIC converter based VFFBSRI with RLC load is designed and simulated using MATLAB/ Simulink and hardware is fabricated.